Core Matrisome Protein Signature During Periodontal Ligament Maturation From Pre-occlusal Eruption to Occlusal Function - Denes, Balazs Jozsef; Ait-Lounis, Aouatef; Wehrle-Haller, Bernhard; Kiliaridis, Stavros (Frontiers in Physiology, 2020)
The pre-occlusal eruption brings the molars into functional occlusion and initiates tensional strains during mastication. We hypothesized that upon establishment of occlusal contact, the periodontal ligament (PDL) undergoes cell and extracellular matrix maturation to adapt to this mechanical function. The PDL of twelve Wistar male rats were laser microdissected to observe the proteomic changes between stages of pre-occlusal eruption, initial occlusal contact and 1-week after occlusion. The proteome was screened by mass spectrometry and confirmed by immunofluorescence. The PDL underwent maturation upon establishment of occlusion. Downregulation of alpha-fetoprotein stem cell marker and protein synthesis markers indicate cell differentiation. Upregulated proteins were components of the extracellular matrix (ECM) and were characterized with the matrisome project database. In particular, periostin, a major protein of the PDL, was induced following occlusal contact and localized around collagen α-1 (III) bundles. This co-localization coincided with organization of collagen fibers in direction of the occlusal forces. Establishment of occlusion coincides with cellular differentiation and the maturation of the PDL. Co-localization of periostin and collagen with subsequent fiber organization may help counteract tensional forces and reinforce the ECM structure. This may be a key mechanism of the PDL to adapt to occlusal forces and maintain structural integrity.